PERHITUNGAN TOTAL BIAYA PERSEDIAAN PUPUK PT. GULA PUTIH MATARAM DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) - , MEIRIZAL PANCA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Gula Putih Mataram is one of sugar cane plantations and sugar industries who requires the control of its fertilizer supplies. The research was conducted in Warehouse Plantation to calculate the economic order quantity of each fertilizer (Urea, TSP, ZA, and KCl) and compare the total inventory cost of companyâs calculation method with Economic Order Quantity (EOQ) method, as well as the efficiency of total inventory cost acquired each fertilizer during April 2012 â March 2013. The analysis result of inventory calculation with EOQ method is known that the economic order quantity of each fertilizer per order during April 2012 â March 2013 sorted from the largest to the smallest is 1.533.655 kgs Urea, 430.126 kgs TSP, 407.362 kgs KCl, and 263.546 kgs ZA. Total inventory cost of each fertilizer during the calculation period based on EOQ method is less than that issued by PT. Gula Putih Mataram. The cost efficiency of Urea is 5,69%, TSP 8,25%, ZA 11,39%, and KCl 43,81%.